2010
DOI: 10.1208/s12248-010-9199-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical Variables Associated with Nonbiodegradable Osmotically Controlled Implants

Abstract: Osmotically controlled implants yield precise zero-order drug delivery kinetics and are utilized in a number of applications. The implants deliver drugs for extended periods (weeks to years) and exhibit good in vivo/in vitro correlation. This paper reviews critical variables associated with these implants, with a focus on release rate testing. The extended-duration kinetics can be problematic when attempting to test for >70% cumulative delivery. An innovative scheme based on the scientific principles of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Osmotically controlled, mechanical devices, “nonbiodegradable” implants have been designed for extended delivery at a constant rate. These systems have been shown to be biocompatible and effective to provide constant therapeutic concentrations in a number of animal and human trials 115-120 . Some of the osmotically-driven implants include Duros® (DURECT), ALZET® (veterinary medicine, research application) and Viadur® (leuprolide acetate, marketed formulation) 120 .…”
Section: Miscellaneous Modes Of Protein Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotically controlled, mechanical devices, “nonbiodegradable” implants have been designed for extended delivery at a constant rate. These systems have been shown to be biocompatible and effective to provide constant therapeutic concentrations in a number of animal and human trials 115-120 . Some of the osmotically-driven implants include Duros® (DURECT), ALZET® (veterinary medicine, research application) and Viadur® (leuprolide acetate, marketed formulation) 120 .…”
Section: Miscellaneous Modes Of Protein Deliverymentioning
confidence: 99%
“…These systems have been shown to be biocompatible and effective to provide constant therapeutic concentrations in a number of animal and human trials 115-120 . Some of the osmotically-driven implants include Duros® (DURECT), ALZET® (veterinary medicine, research application) and Viadur® (leuprolide acetate, marketed formulation) 120 . Precise control over drug release for extended duration (months to year) is achieved by osmotic pressure.…”
Section: Miscellaneous Modes Of Protein Deliverymentioning
confidence: 99%
“…Non-biodegradable silicon-based polymer implants and osmotically driven implants have shown considerable promise in achieving sustained release at constant rates for several proteins and peptides [16, 17]. Although these implants are bio-compatible, a major limitation is the need for surgery to administer and remove the implants.…”
Section: Non-biodegradable Implantsmentioning
confidence: 99%
“…An interesting alternative to accelerated dissolution testing for batch release studies of an extended release implant has been reported by Wright [43] for the Viadur implant. The osmotically‐driven device releases leuprolide acetate for the treatment of prostate cancer over a time span of approximately one year.…”
Section: Prerequisites For Dissolution Testing Of Controlled Release mentioning
confidence: 99%